PARTICIPATION AND PERFORMANCES IN COMPETITIONS: LATVIAN ORIENTEERING DEVELOPMENT EVIDENCE - Smila, Baiba; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Previous efforts to depict sport development opportunities resulted in a sport development metaphor, the participation pyramid (Sotiriadou, Shilbury & Quick, 2008). The base of the sport development metaphor represents the relationship between mass and elite participation (Shilbury, Sotiriadou & Green, 2008) and medals won during the Olympic Games (Sotiriadou, De Bosscher, 2013). The most important international competitions may, therefore, best represent overall sport systems (Sparvero, Chalip, & Green, 2008), but competition opportunities for athletes are the factor contributing to elite success. The aim of this study is to determine the relationship between mass and elite orienteers’ participation and elite orienteers’ performances at the most important national and international orienteering competitions. Methods: the official most important orienteering national and international competition results from 2001 to 2016 were obtained from the websites of each annual organizing committee, linked to the International Orienteering Federation website and mathematical statistics was conducted. The results confirmed a strong, medium and weak relationship between mass and elite orienteers’ participation and elite orienteers’ performances in the most important national and international orienteering competitions. Orienteers’ movement up the participation pyramid is not automatic.